Technologická etapa spodní stavby bytového domu v Trutnově - Bonaventura, Pavel (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Předmětem bakalářské práce byla příprava etapy realizace hrubé spodní stavby bytového domu, který se nachází v Trutnově. Bytový dům je založen na základové konstrukci ze základových pasů z prostého betonu a tvárnic ztraceného bednění. Pro etapu realizace hrubé spodní stavby byly vytvořeny technologické předpisy, navrhnuto zařízení staveniště, zvolena odpovídající strojní sestava, posouzeny dopravní vztahy pro dodávky materiálu a strojů, plán BOZP, kontrolní a zkušební plán, a také byl vytvořen časový harmonogram s rozpočtem.

The bachelor's thesis aimed to prepare the stage of implementation of the rough lower construction of the apartment building which is located in Trutnov. The block of flats is based on a grade construction made of concrete strips footing and construction blocks of pernament formwork. Technological regulations have been created for the stage of realization of the rough lower construction, the equipment of the construction site have been suggested, appropriate machine set has been chosen, shipping relations for material and machine supplies have been considered, OHS (occupational safety and health), control and trial plan have been applied as well as a schedule and budget were created.
Technological stage of the substructure of a residential building in Trutnov
Keywords: bytový dům; hrubá spodní stavba; základové pasy; ztracené bednění; základová deska; zemní práce; bednění; základový trám; technologický předpis; časový plán; výztuž; beton; zařízení staveniště; kontrolní a zkušební plán; strojní sestava; dopravní vztahy; položkový rozpočet; technická zpráva; apartment building; rough construction; concrete strips footing; pernament formwork; grade beam; earthwork; formwork; foundation beam; technological regulation; schedule; reinforcement; concrete; construction site equipment; control and trial plan; machine set; shipping relations; item budget; technical report